Combined lung and liver transplant for cirrhosis, idiopathic pulmonary fibrosis, and hemophilia A: Case report - Lorenzo Olivero; Hong Liang; Ian A. Makey; Si M. Pham; Jorge Sinclair; Stephen Aniskevich, III; Sadia Z. Shah; Dana K. Perry; Wesley L. Allen; Nathan H. Waldron; Liu Yang; Pramod K. Guru; et al. (Transplantation Reports)
Combined lung and liver transplantation (CLLT) is a rare intervention for end-stage lung and liver diseases. It poses a challenge for patients with increased bleeding risk due to Hemophilia A and liver coagulopathy. We present the first documented case of CLLT in an elderly male with Hemophilia A, HCV-associated cirrhosis, and Idiopathic Pulmonary Fibrosis (IPF). Despite the patient exhibiting stable liver function and hemophilia, his lung condition rapidly deteriorated, prompting the listing for transplant. The patient underwent a successful CLLT with perioperative management coordinated by the multidisciplinary team to address the unique challenges of Hemophilia A, resulting in intra-operative correction of coagulopathy. The patient exhibited a favorable recovery, with no requirement for Factor FVIII replacement therapy postoperatively. This case demonstrates that CLLT can address three diseases with distinct pathophysiologies: end-stage lung and liver disease, and correct the hemophilia A phenotype. Our report contributes to the limited literature on the suitability of CLLT in patients with hemophilia A.